Standarisasi Mahar Sebagai Sahnya Perkawinan: (Analisis Terhadap Fiqh Mazhab Imam Syafi’i) - Ikbal, Muhmmad (Ameena Journal, 2024)
Dowry is something that is required in a marriage, one of the five (5) requirement for a valid marriage is dowry. This is a library research methode. In this study, it was found that: Imam Syafi’i sect dowry is something that can be priced, or that can be used as a means of exchenge. Dowry should be concrete objects and can be priced, not to be unclean, swag or loot, should not also stalk of wheat or one date. Dowry is something that is required in a marriage. Dowry may be in the form of debt or bill. Dowry of two types; musamma dowry and mitsil dowry. There is no limit in the number of maximum and minimum levels of dowry, however, it is recommended that dowry is not burdensome or impose, as a wedding blessing that contain marriage dowry is easy and not too expensive. Lessons sharia or dowry is that husband and wife when mixed, to respect women and to be a guide for the wife.